Biaxially oriented polyester film roll

The biaxially stretched polyester film roll addresses issues of wrinkles and defects by controlling tension and contact pressure, using low antimony and specific catalysts, achieving enhanced stability and printability with reduced foreign matter.

JP2024175008AActive Publication Date: 2024-12-17TOYOBO CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024158416
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-02-18
Filing Date
2024-09-12
Publication Date
2024-12-17
Estimated Expiration
2040-02-05

AI Technical Summary

Technical Problem

Existing biaxially oriented polyester films suffer from issues such as wrinkles, misalignment, and uneven deposition during processing, leading to poor gas barrier properties and defects during printing, especially when stored over time, and contain potentially harmful antimony catalyst residues.

Method used

A biaxially stretched polyester film roll with controlled tension and contact pressure during slitting, low antimony content, and specific surface roughness and hardness parameters, along with phosphorus and aluminum-based polymerization catalysts, to enhance stability and reduce foreign matter.

Benefits of technology

The film roll exhibits reduced looseness and defects, maintaining excellent transparency and heat resistance, ensuring long-term storage stability and improved printability without antimony-related health risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024175008000010
    Figure 2024175008000010
  • Figure 2024175008000011
    Figure 2024175008000011
  • Figure 2024175008000012
    Figure 2024175008000012
Patent Text Reader

Abstract

To provide a polyester film roll having excellent printability and processability.SOLUTION: A film roll is made by winding a biaxially oriented polyester film having an antimony content of 10 ppm or less and a phosphorus content of 25 ppm or more and 75 ppm or less, and having an arithmetic mean roughness of the film surface of 0.02 μm or more and 0.05 μm or less, and satisfies the following requirements (1) to (6). (1) The winding length is 8,000 m or more and 80,000 m or less. (2) The width is 500 mm or more and 4,000 mm or les. (3) The average hardness of the outermost layer of the film roll is in the range of 500 or more and 700 or less. (4) The hardness variation of the outermost layer of the film roll is 10% or more and 20% or less. (5) The thickness is 5 μm or more and 40 μm or less. (6) In the thickness unevenness in the film width direction in the surface layer, there are places where the thickness pattern is a recess, and the thickness unevenness of the maximum recess calculated from the maximum thickness difference in the recess with the largest thickness difference (the largest recess) and the average thickness of the film is 10% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biaxially stretched polyester film roll having excellent hygiene, and more particularly to a biaxially stretched polyester film roll which does not develop wrinkles or the like even after long-term storage after film formation, does not cause problems in processing steps such as printing and bag making, and is suitable for use in food packaging bags and labels. [Background technology]

[0002] Polyester resins such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), which are thermoplastic resins with excellent heat resistance and mechanical properties, are used in a wide variety of fields, including plastic films, electronics, energy, packaging materials, automobiles, etc. Among plastic films, biaxially oriented PET film is widely used in industrial and packaging fields because it has an excellent balance between mechanical strength, heat resistance, dimensional stability, chemical resistance, optical properties, and cost.

[0003] In the field of industrial films, due to its excellent transparency, it can be used as a functional film for flat panel displays (FPDs) such as liquid crystal displays and plasma displays. PET films with hydrolysis resistance are also used as backsheet films for solar cells, and are used for various purposes as functional films and base films.

[0004] In the field of packaging films, they are used for food packaging and gas barrier film applications. In particular, films with excellent gas barrier properties are used as packaging materials that require airtightness for foods, medicines, electronic parts, etc., or as gas blocking materials, and demand has been increasing in recent years. In order to impart barrier properties, deposition processing is generally performed using film rolls.

[0005] In recent years, in order to improve productivity, the processing of vapor-deposited polyester films has been accelerated and the film rolls used as the substrate have been made wider and longer. As the rolls become wider and longer, problems such as poor running performance, winding wrinkles, winding misalignment, and spoked wrinkles tend to occur, resulting in localized spots and voids in the vapor-deposited thin film, poor gas barrier properties, and wrinkles occurring during winding after vapor deposition, resulting in poor appearance and making the film unusable as a product, have arisen. Furthermore, packaging bags are often ultimately discarded as waste, and therefore there is a demand for thinner bags to be environmentally friendly. As the thickness is reduced, the film roll loses its stiffness and the film roll loses its appearance during storage after slitting, revealing defects. This causes problems when printing or processing the film roll. In particular, the flatness is poor at the position where slack occurs, and printing defects in the width direction of the film roll cause printing defects, resulting in loss. The present inventors have newly discovered that these problems caused by slack and changes in appearance due to storage are becoming more apparent due to the thinner film, faster printing speed, and more colors, and that it is difficult to apply film rolls that have slack in the film within a range that has not been a problem and has been tolerated in the past.

[0006] As a method for solving such problems, a film roll winding method has been proposed in which the surface pressure of the contact roll is increased in the surface layer portion compared to the surface pressure in the core portion (Patent Document 1). However, although the aforementioned Patent Document 1 describes the winding hardness, winding surface pressure, and winding tension to prevent surface wrinkles, core wrinkles, and winding misalignment, it does not describe any change in the appearance of the film roll due to long-term storage.

[0007] In addition, food packaging films come into direct contact with food, so from the standpoint of hygiene, it is desirable for the polyester film to have as little foreign matter as possible. In addition, since the antimony catalyst used in the process of producing (polymerizing) polyester raw materials is potentially carcinogenic, it is desirable for the polyester film to contain as little antimony as possible or none at all. Conventionally, as described in Patent Documents 2 and 3, for example, there are polyester raw materials that do not use antimony catalysts. However, there is no description of a method for reducing film foreign matter or the desired film properties. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Publication No. 63-252853 [Patent Document 2] Patent No. 3461175 [Patent Document 3] Patent No. 3506236 [Patent Document 4] JP 2001-151907 A Summary of the Invention [Problem to be solved by the invention]

[0009] The object of the present invention is to provide a biaxially oriented polyester film roll which has an extremely low antimony content, a small amount of foreign matter, excellent transparency and heat resistance, and is not prone to loosening of the film roll immediately after film formation, and is also not prone to loosening of the film roll over time even when stored for a long period of time, and is less likely to cause defects during printing processing. [Means for solving the problem]

[0010] As a result of extensive research, the present inventors have discovered that, without using antimony, in the slitting process in which a polyester film having a desired surface roughness is slit from a master roll to a desired width to produce a product roll, by controlling the winding tension after slitting and the contact pressure of the contact roll, it is possible to bring the hardness of the roll within the above-mentioned range, and that the film roll is less likely to sag after long-term storage, thereby completing the present invention. The present invention comprises the following configurations.

[0011] 1. A biaxially oriented polyester film roll comprising a wound biaxially oriented polyester film having an antimony content of 10 ppm or less, a phosphorus content of 25 ppm or more and 75 ppm or less, and an arithmetic mean roughness of the film surface of 0.02 μm or more and 0.05 μm or less, the biaxially oriented polyester film and the film roll satisfying the following requirements (1) to (6): (1) The length of the film roll is between 8,000 m and 80,000 m. (2) Film roll width is 500 mm or more and 4000 mm or less (3) The hardness of the outermost layer of the film roll is in the range of 500 to 700 on average when measured at intervals of 50 mm in the width direction of the film. (4) The hardness of the outermost layer of the film roll is measured at intervals of 50 mm in the width direction of the film, and the variation in hardness is 10% or more and 20% or less. (5) Film thickness is 5 μm or more and 40 μm or less (6) In the thickness unevenness in the film width direction on the surface layer of the film roll, the thickness pattern has a concave portion, and in the concave portion with the largest thickness difference (maximum concave portion), the thickness unevenness of the maximum concave portion calculated from the maximum thickness difference in the maximum concave portion and the average thickness of the film is less than 10%. 2. A biaxially stretched polyester film roll according to 1, in which the thickness unevenness in the width direction of the film of each sample sampled at 1000 m intervals along the length of the film roll from the surface layer is 10% or less for all samples, as calculated from the maximum thickness difference at the maximum concave portion and the average thickness of the film. 3. The biaxially stretched polyester film roll according to any one of 1. to 2., wherein the absolute value of the difference in refractive index in the width direction between the maximum recess and either of the maximum thickness points at both ends of the recess is 0.010 or less. 4. A biaxially stretched polyester film roll according to any one of 1. to 3., characterized in that the number of defects of 1 mm or more per 10,000 square meters of film is 1.0 or less. 5. The biaxially stretched polyester film roll according to any one of 1. to 4., wherein the static friction coefficient and the dynamic friction coefficient of the outer surface and the inner surface of the film roll are both 0.1 or more and 0.8 or less. 6. The biaxially stretched polyester film roll according to any one of 1. to 5., wherein the intrinsic viscosity of the film is 0.51 dl / g or more and 0.70 dl / g or less. 7. A method for producing a biaxially oriented polyester film roll according to any one of 1. to 6., comprising melt-extruding a raw polyester resin so that the difference between the intrinsic viscosity of the raw polyester resin and the intrinsic viscosity of the polyester film is 0.06 dl / g or less, followed by cooling and solidifying to obtain an unstretched film, biaxially stretching the unstretched film, subjecting it to a heat setting treatment, winding up the biaxially stretched film as a master roll, and then slitting and winding up the master roll into a roll. Effect of the Invention

[0012] According to the present invention, a biaxially oriented polyester film roll can be provided which has an extremely low antimony content, a small amount of foreign matter, excellent transparency and heat resistance, and is not prone to loosening of the film roll immediately after film formation, and is also not prone to loosening over time even when stored for a long period of time, and is less likely to cause defects during printing processing. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a diagram showing the maximum concave portion in the thickness unevenness in the width direction of the film of the present invention. [Diagram 2]FIG. 2 is a diagram showing an example of a film transverse stretching (TD) step of the present invention. [Diagram 3] FIG. 2 is a diagram showing an example of a cooling step in the film transverse stretching (TD) step of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The following describes an embodiment of the present invention. However, the present invention should not be construed as being limited to the embodiment including the following examples, and various modifications are possible as long as the object of the invention can be achieved and the gist of the invention is not deviated from.

[0015] (Raw polyester resin) The biaxially stretched polyester film of the present invention is composed of a polyethylene terephthalate resin. Here, the polyethylene terephthalate resin contains an ethylene glycol-derived component and a terephthalic acid-derived component as main components. The "main components" means that terephthalic acid accounts for 80 mol% or more of 100 mol% of all dicarboxylic acid components, and ethylene glycol accounts for 80 mol% or more of 100 mol% of all glycol components.

[0016] Other dicarboxylic acid components and glycol components may be copolymerized within a range that does not impair the object of the present invention. The copolymerization amount of other dicarboxylic acid components and glycol components is less than 20 mol %, preferably 10 mol % or less, and particularly preferably 5 mol % or less, based on the total dicarboxylic acid components or the total glycol components, respectively. Examples of the other dicarboxylic acid components include aromatic dicarboxylic acids such as isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, and 5-sodium sulfoisophthalic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 2,5-norbornenedicarboxylic acid, and tetrahydrophthalic acid; and aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, octadecanedioic acid, fumaric acid, maleic acid, itaconic acid, mesaconic acid, citraconic acid, and dimer acid.

[0017] Examples of the other glycol components include aliphatic glycols such as 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, 2-amino-2-ethyl-1,3-propanediol, 2-amino-2-methyl-1,3-propanediol, 1,10-decanediol, dimethyloltricyclodecane, diethylene glycol, and triethylene glycol; alicyclic glycols such as bisphenol A, bisphenol S, bisphenol C, bisphenol Z, bisphenol AP, ethylene oxide adducts or propylene oxide adducts of 4,4'-biphenol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol; polyethylene glycol; and polypropylene glycol.

[0018] As a polymerization method for such a polyethylene terephthalate-based resin, any production method can be used, such as a direct polymerization method in which terephthalic acid is directly reacted with ethylene glycol, and, if necessary, other dicarboxylic acid components and glycol components, and an ester exchange method in which a dimethyl ester of terephthalic acid (containing, if necessary, a methyl ester of another dicarboxylic acid) is directly reacted with ethylene glycol (containing, if necessary, other glycol components), followed by a polycondensation reaction.

[0019] As the polyester resin, recycled resin made from recycled PET bottles and polyester resin containing a monomer component derived from biomass can also be used.

[0020] The biaxially oriented polyester film of the present invention may contain other resins such as polyamide, polystyrene, polyolefin, and polyesters other than those mentioned above as components. However, in terms of the mechanical properties and heat resistance of the biaxially oriented polyester film, the content of other resins is preferably 30 mass% or less, more preferably 20 mass% or less, or even 10 mass% or less, and particularly preferably 5 mass% or less, based on the total resin components of the polyester film, and is most preferably 0 mass% (all resin components constituting the polyester film are essentially polyethylene terephthalate-based resins).

[0021] The intrinsic viscosity of the polyethylene terephthalate resin is preferably in the range of 0.57 to 0.76 dl / g, more preferably 0.60 to 0.73 dl / g, and further preferably 0.63 to 0.70 dl / g. If the intrinsic viscosity is lower than 0.57 dl / g, the polyester film is likely to tear during production (so-called breakage occurs), whereas if it is higher than 0.76 dl / g, the filtration pressure increases significantly, making high-precision filtration difficult, and it is likely to be difficult to extrude the resin through the filter. The intrinsic viscosity of the resin of the polyester film is preferably in the range of 0.51 to 0.70 dl / g, more preferably 0.56 to 0.68 dl / g, and further preferably 0.59 to 0.65 dl / g. If the intrinsic viscosity is lower than 0.51 dl / g, the polyester film is likely to tear during processing such as printing, and if the intrinsic viscosity is higher than 0.76 dl / g, the effect of improving the mechanical properties is likely to become saturated.

[0022] (Polymerization catalyst) Next, the polymerization catalyst used in producing the raw material polyester resin used in the present invention will be described. The polymerization catalyst used in the present invention is characterized by having the ability to promote esterification. In the present invention, as described later, it is preferable to avoid the use of polymerization catalysts of antimony compounds such as antimony trioxide that have been conventionally used. As such a polymerization catalyst, a polymerization catalyst containing at least one selected from aluminum compounds and at least one selected from phosphorus-based compounds is preferable.

[0023] As the aluminum compound constituting the polymerization catalyst used in synthesizing the raw material polyester resin used in the present invention, any known aluminum compound can be used without any limitation.

[0024] Specific examples of aluminum compounds include aluminum acetate, basic aluminum acetate, aluminum lactate, aluminum chloride, aluminum hydroxide, aluminum hydroxide chloride, aluminum acetylacetonate, aluminum oxalate, and other organic aluminum compounds and partial hydrolysates thereof. Of these, carboxylates, inorganic acid salts, and chelate compounds are preferred, and among these, aluminum acetate, basic aluminum acetate, aluminum lactate, aluminum chloride, aluminum hydroxide, aluminum hydroxide chloride, and aluminum acetylacetonate are more preferred, aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, and aluminum hydroxide chloride are even more preferred, and aluminum acetate and basic aluminum acetate are most preferred.

[0025] The amount of the aluminum compound used in the polymerization catalyst according to the present invention is preferably 1 to 80 ppm, more preferably 2 to 60 ppm, still more preferably 3 to 50 ppm, particularly preferably 5 to 40 ppm, and most preferably 10 to 30 ppm, in terms of aluminum atoms remaining relative to the total mass of the resulting polyester resin. If the content is lower than the above range, the catalytic activity may be poor, whereas if the content is higher than the above range, it may cause the formation of aluminum-based foreign matter. Even when the aluminum compound is placed in a reduced pressure environment during polyester polymerization, almost 100% of the amount used remains, so it can be considered that the amount used is the residual amount.

[0026] The phosphorus compound used in the polymerization catalyst is not particularly limited, but the use of a phosphonic acid compound or a phosphinic acid compound is preferable because it has a large effect of improving the catalytic activity, and among these, the use of a phosphonic acid compound is particularly preferable because it has a large effect of improving the catalytic activity.

[0027] Among these phosphorus compounds, phosphorus compounds having a phenol moiety in the same molecule are preferred. There are no particular limitations on the phosphorus compounds having a phenol structure, but using one or more compounds selected from the group consisting of phosphonic acid compounds and phosphinic acid compounds having a phenol moiety in the same molecule is preferred because it has a large effect of improving catalytic activity. Among these, using one or more phosphonic acid compounds having a phenol moiety in the same molecule is particularly preferred because it has a large effect of improving catalytic activity.

[0028] Examples of phosphorus compounds having a phenol moiety in the same molecule include compounds represented by the following general formulas (Chemical Formula 1) and (Chemical Formula 2).

[0029] [ka]

[0030] [ka]

[0031] (In formulas (chemical formula 1) to (chemical formula 2), R 1 R represents a hydrocarbon group having 1 to 50 carbon atoms and containing a phenol moiety, or a hydrocarbon group having 1 to 50 carbon atoms and a substituent such as a hydroxyl group, a halogen group, an alkoxyl group, or an amino group and containing a phenol moiety. 4R represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms containing a substituent such as a hydroxyl group, a halogen group, an alkoxyl group, or an amino group. 2 , R 3 R each independently represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms containing a substituent such as a hydroxyl group or an alkoxyl group. However, the hydrocarbon group may contain a branched structure, an alicyclic structure such as cyclohexyl, or an aromatic ring structure such as phenyl or naphthyl. 2 and R 4 The ends of may be bonded together.)

[0032] Examples of the phosphorus compound having a phenol moiety in the same molecule include p-hydroxyphenylphosphonic acid, dimethyl p-hydroxyphenylphosphonate, diethyl p-hydroxyphenylphosphonate, diphenyl p-hydroxyphenylphosphonate, bis(p-hydroxyphenyl)phosphinic acid, methyl bis(p-hydroxyphenyl)phosphinate, phenyl bis(p-hydroxyphenyl)phosphinate, p-hydroxyphenylphenylphosphinic acid, methyl p-hydroxyphenylphenylphosphinate, phenyl p-hydroxyphenylphosphinate, p-hydroxyphenylphosphinic acid, methyl p-hydroxyphenylphosphinate, phenyl p-hydroxyphenylphosphinate, etc. In addition, phosphorus compounds represented by the following general formula (Chemical Formula 3) can be mentioned.

[0033] [ka]

[0034] In the formula (Chemical Formula 3), X1 and X2 each represent a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a monovalent or higher metal. In addition, X1 may be a metal having a valence of 2 or more, and X2 may not be present. Furthermore, an anion corresponding to the excess valence of the metal may be disposed relative to the phosphorus compound. As the metal, Li, Na, K, Ca, Mg, and Al are preferred.

[0035] By adding these phosphorus compounds having a phenol moiety in the same molecule during polyester polymerization, the catalytic activity of the aluminum compound is improved and the thermal stability of the polymerized copolymer polyester resin is also improved.

[0036] Among the above, the phosphorus compound preferably used as the polycondensation catalyst is at least one phosphorus compound selected from the compounds represented by chemical formula (4) and chemical formula (5).

[0037] [ka]

[0038] [ka]

[0039] As the compound represented by the above chemical formula (Chemical Formula 4), Irganox1222 (manufactured by BASF) is commercially available. As the compound represented by the above chemical formula (Chemical Formula 5), ​​Irganox1425 (manufactured by BASF) is commercially available and can be used.

[0040] The amount of the phosphorus compound used in the polymerization catalyst according to the present invention is preferably such that 10 to 100 ppm, more preferably 15 to 90 ppm, still more preferably 20 to 80 ppm, particularly preferably 25 to 70 ppm, and most preferably 30 to 60 ppm remain as phosphorus atoms relative to the total mass of the resulting raw material polyester resin. If phosphorus atoms remain in an amount exceeding the upper or lower limit above, the polymerization activity may decrease. When the phosphorus compound is placed in a reduced pressure environment during polyester polymerization, approximately 10 to 30% of the amount used is removed from the system depending on the conditions. Therefore, in practice, it is necessary to carry out several trial experiments to determine the residual rate of the phosphorus compound in the polyester and then determine the amount used.

[0041] In addition, the use of the phosphorus compound can improve the heat resistance of the resin. Although the reason is not clear, it is believed that the hindered phenol moiety in the phosphorus compound improves the heat resistance of the copolymer polyester resin.

[0042] If the residual amount of the phosphorus compound is less than 10 ppm, the above-mentioned effect of improving heat resistance is weakened, and as a result, the effect of improving the heat resistance and coloring of the copolymerized polyester resin of the present invention may not be observed.

[0043] In order to further improve the catalytic activity within a range that does not impair the effects of the present invention, metal-containing polycondensation catalysts such as antimony compounds, titanium compounds, tin compounds, and germanium compounds may be used in combination. In that case, the antimony compounds are preferably 10 ppm or less as antimony atoms relative to the mass of the obtained copolymerized polyester resin, the germanium compounds are preferably 10 ppm or less as germanium atoms relative to the mass of the obtained copolymerized polyester resin, the titanium compounds are preferably 3 ppm or less as titanium atoms relative to the mass of the obtained copolymerized polyester resin, and the tin compounds are preferably 3 ppm or less as tin atoms relative to the mass of the obtained polyester resin. From the purpose of the present invention, it is preferable to avoid using metal-containing polycondensation catalysts such as these antimony compounds, titanium compounds, tin compounds, and germanium compounds as much as possible.

[0044] In the present invention, in addition to the aluminum compound, a small amount of at least one selected from alkali metals, alkaline earth metals, and compounds thereof may be coexisted as a second metal-containing component. The coexistence of such a second metal-containing component in the catalyst system not only suppresses the production of diethylene glycol, but also enhances catalytic activity, thereby obtaining a catalyst component with a higher reaction rate, which is effective in improving productivity. When an alkali metal, an alkaline earth metal, or a compound thereof is added in combination, the amount used (mol%) is preferably 1×10 to 10 moles of the dicarboxylic acid component constituting the polyester resin. -5Even if the alkali metal, alkaline earth metal, or compound thereof is placed in a reduced pressure environment during polyester polymerization, almost 100% of the amount used remains, so the amount used can be considered to be the residual amount.

[0045] The polymerization catalyst according to the present invention has catalytic activity not only in polycondensation reactions but also in esterification reactions and transesterification reactions. Transesterification reactions between alkyl esters of dicarboxylic acids such as dimethyl terephthalate and glycols such as ethylene glycol are usually carried out in the presence of transesterification catalysts such as zinc, but the catalyst according to the present invention can be used instead of these catalysts. The polymerization catalyst according to the present invention also has catalytic activity not only in melt polymerization but also in solid-phase polymerization and solution polymerization.

[0046] The polymerization catalyst for polyester used in the present invention can be added to the reaction system at any stage of polymerization reaction. For example, it can be added to the reaction system before the start of esterification reaction or transesterification reaction or at any stage during the reaction, immediately before the start of polycondensation reaction, or at any stage during polycondensation reaction. In particular, it is preferable to add the aluminum compound and phosphorus compound according to the present invention immediately before the start of polycondensation reaction.

[0047] (Preferred Method for Producing Biaxially Stretched Polyester Film) The biaxially stretched polyester film of the present invention may have a laminated structure of one layer, two layers, three layers, or four or more layers. In the case of a two-layer or more layer structure, each layer contains the polyethylene terephthalate resin, inorganic particles, and a resin other than the polyethylene terephthalate resin as described above as constituent components, but it is preferable that the types or contents of any of the constituent components of adjacent layers are different from each other. In the case of a single-layer structure consisting of layer A, layer A in the present invention corresponds to the entire biaxially oriented polyester film. In the case of a two-layer structure including layer A, the layer A in the present invention refers to either one or both layers. In the case of a three-layer structure, the layer A in the present invention refers to either one layer or two layers, the outer layers on both sides.

[0048] In particular, in the case of a three-layer structure, even if there are no inorganic particles in the inner layer, the surface roughness of the film can be controlled by controlling the amount of added particles only in the surface layer, and the content of inorganic particles in the film can be reduced, which is preferable. This is because it also improves the problem of odor components escaping through voids (spaces) that form at the boundary between the inorganic particles and the polyester resin, resulting in a decrease in aroma retention. Furthermore, it is easy to use recycled raw materials from trimmed edges produced during the film production process or recycled raw materials from other film production processes in the inner layer section, as long as it does not adversely affect the characteristics of the film surface, which is also advantageous in terms of cost.

[0049] Examples of the inorganic particles that can be used include silica, alumina, titanium dioxide, calcium carbonate, kaolin, and barium sulfate. The average particle size of the inorganic particles is preferably within the range of 0.05 to 3.0 μm when measured with a Coulter counter. The lower limit of the inorganic particle content in the film is preferably 0.01% by weight, more preferably 0.015% by weight, and even more preferably 0.02% by weight. If it is less than 0.01% by weight, the slipperiness may decrease. The upper limit is preferably 1% by weight, more preferably 0.2% by weight, and even more preferably 0.1% by weight. If it exceeds 1% by weight, the transparency may decrease, which is not very preferable.

[0050] As a method for incorporating inorganic particles into polyester, for example, inorganic particles are dispersed in a predetermined ratio in ethylene glycol, which is a diol component, in the form of a slurry, and this ethylene glycol slurry is added at an arbitrary stage before the completion of polyester polymerization. When adding particles, for example, it is preferable to add the aqueous sol or alcohol sol obtained during particle synthesis without first drying it, since this provides good dispersibility of the particles and prevents the generation of coarse protrusions. It is also effective to directly mix the aqueous slurry of the particles with a given polyester pellet, feed the mixture to a vented twin-screw kneading extruder, and knead the mixture into the polyester.

[0051] In the present invention, it is preferable to extrude the resin at a temperature of the extruder that is at least 2°C above the melting point of the resin and not more than 6°C above the melting point of the resin. If the extrusion temperature is less than 2°C above the melting point, the resin will not melt and unmelted material will be discharged, which will become foreign matter, which is not preferable. Also, if the resin is extruded at a temperature higher than the melting point +6°C, the resin will thermally deteriorate and cause the generation of foreign matter, which is not preferable.

[0052] The extruded sheet-like molten resin is then extruded through a T-die and quenched to obtain an unstretched film. As a method for quenching the molten resin, a method in which the molten resin is cast from a T-die onto a rotating drum and quenched and solidified to obtain a substantially unoriented resin sheet can be suitably adopted. In addition, sublimated products of the molten resin (oligomers, etc.) tend to adhere to the T-die, and if the adhered products fall off, they will adhere to the unstretched sheet and become foreign matter in the film, which is undesirable. Therefore, it is preferable to attach an adhesive sheet to the T-die in advance to prevent the sublimated products from falling off, and to clean the cooling roll with a cleaner during operation so that even if foreign matter adheres to the cooling roll, it will not be transferred to the unstretched sheet.

[0053] The unstretched film thus obtained is then biaxially stretched, followed by heat setting and heat relaxation. By appropriately combining the following film-forming conditions, such as the longitudinal and transverse stretching conditions, heat setting conditions, and heat relaxation conditions, it is possible to achieve the preferred film properties described below. These are explained in detail below.

[0054] The stretching method can be either simultaneous biaxial stretching or sequential biaxial stretching, but sequential biaxial stretching is preferred from the viewpoint of high film-forming speed and high productivity. In the following, a sequential biaxial stretching method by longitudinal stretching-transverse stretching in which longitudinal stretching is performed first and then transverse stretching is performed will be described. It may be stretched longitudinally.

[0055] The stretching temperature in the longitudinal (machine) direction (hereinafter sometimes abbreviated as MD) is preferably (Tg+5) to (Tg+55)°C, and the stretching ratio is preferably 3 to 5 times, from the viewpoint of reducing bowing. If the stretching temperature is higher than (Tg+55)°C or lower than 3 times, although bowing is reduced, the orientation in the longitudinal direction becomes insufficient, and thickness unevenness in the longitudinal direction worsens, which is not preferable. In addition, the planarity of the obtained biaxially stretched polyester film is also deteriorated, which is not preferable. On the other hand, if the temperature is lower than (Tg+5)°C or higher than 5 times, the shrinkage stress increases, and bowing increases, which is not preferable.

[0056] In addition, in the longitudinal stretching, in a method of stretching in multiple stages between multiple rolls rather than in one stage, the film is gradually stretched in the longitudinal direction while controlling the stretching speed, so that the difference in physical properties in the film width direction can be reduced. Two-stage to five-stage stretching is preferable from the viewpoints of effect, equipment, and cost.

[0057] When stretching in the width (transverse) direction (hereinafter sometimes abbreviated as TD), the unstretched film is introduced into a tenter device which can heat the film by holding both ends of the film with clips, and the film is heated to a predetermined temperature with hot air. After that, the film is stretched in the width direction by increasing the distance between the clips while transporting it in the longitudinal direction. Also, if the stretching temperature in the width direction is less than Tg+5°C, breakage is likely to occur during stretching, which is not preferred. Also, if it is higher than Tg+70°C, uniform stretching in the width direction is not possible, and uneven thickness in the width direction increases, which is not preferred because the hardness of the film roll varies widely. More preferably, the temperature is Tg+10°C or more and Tg+65°C or less, and even more preferably, the temperature is Tg+15°C or more and Tg+60°C or less. The stretching ratio in the width direction is not particularly specified, but is preferably 3 times or more and 7 times or less. If the stretching ratio is less than 3 times, the productivity will be poor, and the orientation in the width direction will be insufficient, resulting in uneven thickness in the width direction, and uneven hardness in the width direction of the film roll will occur, which is not preferable. If the stretching ratio exceeds 7 times, the film will be easily broken during stretching and film formation, which is not preferable. In addition, it is preferable to stretch in multiple stages such as two or three stages, as this improves uneven thickness in the width direction.

[0058] The heat setting temperature (heat treatment temperature) after TD stretching is preferably 230 to 255°C. If the heat setting temperature is higher than 255°C, it is not preferable because the film melts and breaks due to the proximity of the melting point of the polyester resin. It is also not preferable because the film surface becomes rough and white due to melting, impairing transparency. On the other hand, if it is lower than 230°C, it is not preferable because the heat shrinkage rate increases in both the longitudinal and transverse directions, and the thermal dimensional stability during deposition processing deteriorates.

[0059] In the heat relaxation process, the film is in a state where it is very easy to move up and down because the binding force in the width direction is reduced and the film may slacken under its own weight or the accompanying air current may cause the film to expand. Therefore, in this heat relaxation process, the change in the orientation angle and the difference in the oblique heat shrinkage rate of the obtained biaxially oriented polyester film varies greatly depending on the film transport state. For example, a method of reducing this is to keep the film parallel by appropriately adjusting the wind speed blown from the upper and lower nozzles. The heat relaxation rate in the width direction is preferably 4 to 8%. If the heat relaxation rate is less than 4%, the heat shrinkage rate in the width direction of the obtained biaxially oriented polyester film becomes high, which is undesirable because the dimensional stability during deposition processing becomes poor. On the other hand, if the heat relaxation rate is more than 8%, bowing increases, slackness, etc. occurs, and the thickness unevenness in the width direction becomes large, which is undesirable because the hardness of the film roll becomes uneven.

[0060] Furthermore, when the heat-treated film is cooled in the TD, oligomers are generated. If the oligomers adhere to the film, they become defects and cause printing defects, which is undesirable. Therefore, it is preferable to remove the oligomers in the TD or at the TD exit using an adhesive roll or the like. A specific example of oligomer removal is shown in Figure 3. Simply blowing cooling air onto the film will generate oligomers, which will then float around in the zone and adhere to the film. Therefore, by installing a plenum duct to suck in the oligomers after blowing cooling air, the amount of oligomers floating around in the zone is reduced, making it more difficult for the oligomers to adhere to the film.

[0061] The film stretched and formed by the above method is wound up by a winder device to produce a master roll. The film is then slit to a specified width and length using a slitter and wound around a winding core to obtain a biaxially stretched polyester film roll. As the winding core, a plastic core, a metal core, or a paper core of 3 inches, 6 inches, 8 inches, etc. can usually be used. The preferred winding length and width of the film roll are as described above. In addition, it is preferable to reduce slack that occurs during slitting by adopting the following slitting conditions.

[0062] Specific slitting conditions are an initial tension of 70 to 160 N / m, preferably 80 to 150 N / m, and an initial surface pressure of 200 to 400 N / m, preferably 250 to 350 N / m, at which slitting is started. If the initial tension is higher than 160 N / m, the uneven thickness of the recessed portion is slightly stretched by the tension during slitting, which is undesirable as it causes slackness. If the initial tension is 70 N / m or less, the tension is insufficient when the film is wound up by slitting, which causes the end surface of the film roll to become uneven (so-called end surface misalignment), which is undesirable. In addition, it is desirable to reduce the tension after the winding length reaches 500 m. Specifically, it is desirable to reduce the tension consistently so that it correlates with the winding length, so that the tension 300 m before the end of slitting is 50 to 80%, preferably 60 to 70%, of the initial tension. In addition, it is preferable to keep the surface pressure as constant as possible over the entire winding length. The initial surface pressure is preferably within ±5% over the entire winding length, and more preferably within ±3%.

[0063] In general, in industrially produced film rolls, a film that has been continuously produced is continuously wound up, and if the film production conditions are constant, the degree of thickness unevenness in the film width direction is almost constant over the entire length of the winding, but due to minute fluctuations in each process during film production, some fluctuations occur over the entire length of the winding. It is preferable that the thickness unevenness in the film width direction is controlled over the entire length of the winding. Whether the thickness unevenness is controlled over the entire length of the winding can be confirmed, for example, by taking samples of the film of the film roll from the surface layer at regular intervals for each winding length and measuring the thickness unevenness of each sample. In the film roll of the present invention, the thickness unevenness can be measured by taking samples of the surface layer part of the film roll and using them as a representative value for the film roll. In the present invention, as described in the examples described later, a sample is taken from a part where 5 m of the film is removed from the surface layer of the film roll, and the representative value is measured. The preferred range of thickness unevenness in the film width direction (maximum recessed part and thickness unevenness in the entire width direction) on the surface layer of the film roll is as described above. In a preferred embodiment of the present invention, samples are taken every 1000 m of the roll length and measured, and the thickness unevenness (thickness unevenness at the maximum recess and the entire width direction) of all samples is within a predetermined range. The preferred range of thickness unevenness in the film width direction (thickness unevenness at the maximum recess and the entire width direction) over the entire length of the film roll is as described above.

[0064] (Structure and properties of biaxially oriented polyester film) The biaxially stretched polyester film of the present invention preferably has an antimony content of 10 ppm or less. Since antimony is a substance of concern for its carcinogenicity, the smaller the amount, the better, preferably 5 ppm, and more preferably 0 ppm. The antimony content of the raw material resin used in the present invention is preferably 0 ppm, but there is a possibility that antimony may be mixed in during production, so the content is set to 10 ppm or less.

[0065] In the biaxially stretched polyester film of the present invention, the difference between the intrinsic viscosity of the polyester resin and the intrinsic viscosity of the polyester film is preferably 0.06 dl / g or less. The difference in intrinsic viscosity is an index of the degree of deterioration when the polyester resin is melt-extruded. If it is higher than 0.06 dl / g, the resin deteriorates in the extruder, which causes foreign matter, and is not preferable. The intrinsic viscosity difference is preferably 0 dl / g, but it is difficult to make it 0 dl / g because it is substantially melted. It is preferably 0.05 dl / g or less, and more preferably 0.04 dl / g or less. In order to control the difference in intrinsic viscosity as described above, in the present invention, it is preferable to extrude the resin at a resin melting point +2°C or more and a resin melting point +6°C or less. If the extrusion temperature is less than the melting point +2°C, the resin does not melt and unmelted material is discharged, which becomes foreign matter, and this is not preferable. If the resin is extruded at a temperature higher than the melting point +6°C, the resin deteriorates thermally and becomes foreign matter, and this is not preferable.

[0066] The biaxially oriented polyester film of the present invention preferably has one or less defects of 1 mm or more per 10,000 square meters. By reducing the number of defects of 1 mm or more per 1,000 square meters in this manner, printability becomes very good. If the number of defects due to foreign matter is large, ink loss occurs during printing, which is undesirable. The fewer the number of defects of 1 mm or more, the more preferable, with 0.5 or less being more preferable, 0.3 or less being even more preferable, 0.1 or less being particularly preferable, and 0 being the most preferable. In the present invention, the number is set to one or less because there is a possibility that foreign matter may be mixed in during an unexpected trouble.

[0067] The arithmetic mean roughness of the surface of the biaxially stretched polyester film of the present invention is preferably 0.02 μm or more and 0.05 μm or less. If it is less than 0.02 μm, blocking occurs due to adhesion of the film in the film roll, and abnormal noise (sound of the adhered film peeling off) occurs during unwinding, or the film breaks, which is not preferable. Also, if it exceeds 0.05 μm, it is not preferable because the evaporated thin film is likely to come off during processing such as deposition, and the gas barrier property is deteriorated.

[0068] The thickness of the biaxially oriented polyester film of the present invention is preferably 5 μm or more and 40 μm or less. The upper limit of the film thickness is more preferably 35 μm or less, and even more preferably 30 μm or less. Since the thickness confirmed in the present invention was up to 5 μm, the lower limit of the thickness was set to 5 μm or more. In addition, the thicker the film, the more stiff it is and the less slack it tends to be, so it is not a problem if it is thick, but it goes against the environmental friendliness of making the film thinner. In addition, the thinner the film, the more likely it is to cause slack, so in the embodiment of the present invention, making the film thinner is more difficult.

[0069] In addition, the static friction coefficient and dynamic friction coefficient between the film surfaces of the outer and inner surfaces of the biaxially oriented polyester film of the present invention are preferably 0.1 to 0.8. If it is lower than 0.1, the film may slip too much and cause the end surfaces to slip. If it is higher than 0.8, the amount of air entrained during slitting increases, and the film roll is prone to slackness and wrinkles due to air loss from the recesses. It is preferably 0.13 to 0.77, more preferably 0.16 to 0.74.

[0070] (Characteristics of biaxially oriented polyester film roll) The winding length of the biaxially oriented polyester film roll of the present invention is preferably 8000 m or more and 80000 m or less. In processing such as printing and deposition, the longer the winding length, the less frequently the roll needs to be replaced and the better the work efficiency. It is preferably 10000 m or more, more preferably 12000 m or more, and particularly preferably 14000 m or more. There is no particular upper limit, and the longer the winding length, the more preferable it is, but since the inventors have only confirmed a winding length up to 80000 m, the winding length of 80000 m is set as the upper limit. Note that, as the winding length of the film roll becomes longer, the area of ​​the film increases and the chance of the defect of slackness occurring increases, so in the embodiment of the present invention, a long winding length of the film roll is more difficult.

[0071] The width of the biaxially oriented polyester film roll of the present invention is preferably 500 mm or more and 4000 mm or less. There is no particular upper limit, and a longer width of the film roll is preferable because it reduces loss in the printing process, but the inventors have only confirmed a width of 4000 mm, so the upper limit is set to 4000 mm. In addition, the wider the film roll, the higher the efficiency of processing such as printing, as described above, so the wider the width, the more preferable it is. The preferred width is 700 mm or more, more preferably 900 mm or more, and particularly preferably 1100 mm or more. In addition, the longer the width of the film roll, the greater the area of ​​the film and the greater the chance of the defect of slack occurring, so in the embodiment of the present invention, a longer width of the film roll is more difficult.

[0072] Furthermore, the biaxially stretched polyester film roll of the present invention has a portion where the thickness pattern is a concave in the thickness unevenness in the width direction of the film roll, and in the concave portion with the largest thickness difference (maximum concave portion), the thickness unevenness of the maximum concave portion calculated from the maximum thickness difference at the maximum concave portion and the average thickness of the film according to the following formula 1 is preferably 10% or less (an example is shown in FIG. 1). Uneven thickness of recess = (Maximum height of recess - Minimum height of recess) ÷ Average thickness ×100(%) ···Formula 1

[0073] In the present invention, the recess refers to a thickness pattern portion of a peak-valley-peak, in which a peak is a point at which the thickness decreases in both directions of the measurement direction and a valley is a point at which the thickness increases in both directions of the measurement direction, as described later, in thickness unevenness in the film width direction measured using a continuous contact thickness meter. Films that do not have such a thickness pattern, i.e., films that do not have recesses, are not included in the present invention. In two peaks and one valley in a recess, the greater of the thickness differences between the peaks and valleys (if the values ​​are the same, both values) is referred to as the maximum thickness difference in the recess.

[0074] If the thickness unevenness of the maximum recess is more than 10%, air is trapped and accumulated when the recess is slit and wound into a film roll, and air escapes during storage of the film roll, which is undesirable as it causes wrinkles and slack. In addition, the recess is thinner than other parts in the width direction, so it is stretched in the longitudinal direction by the tension when slitting and winding into a film roll. Therefore, the length of the recess in the longitudinal direction of the film roll becomes longer than other parts in the width direction, and the part becomes slack. The present inventors' investigation has revealed that this is particularly evident when the thickness difference between the recess and both ends is large. The preferred maximum recess thickness unevenness is 9% or less, and more preferably 8% or less. The lower the maximum recess thickness unevenness, the more preferable, and the lowest thickness unevenness was 3% in the inventors' tests.

[0075] The thickness unevenness of the recesses as described above should be measured using a continuous contact thickness gauge as shown in the following examples. For example, as shown in Patent Document 4, if the thickness is measured at intervals of 30 mm to 500 mm in the measurement direction, the maximum thickness difference of the recesses may be at an unmeasured position, making it difficult to obtain the thickness difference at the accurate recesses. The thickness unevenness in the present invention refers to the one measured using a continuous contact thickness gauge.

[0076] In addition, in the thickness unevenness in the width direction of the film of each sample sampled at 1000 m intervals along the winding length from the surface layer of the biaxially oriented polyester film roll of the present invention, it is preferable that the thickness unevenness calculated from the maximum thickness difference at the maximum recess and the average thickness of the film is 10% or less for all samples.

[0077] As mentioned above, if the maximum thickness unevenness of the recess is more than 10%, air is trapped and accumulated when the recess is slit and wound into a film roll, and air escapes during storage of the film roll, which is undesirable as it causes wrinkles and slack. In addition, the recess is thinner than other parts in the width direction, so it is stretched in the longitudinal direction by the tension during slitting. Therefore, the length of the recess in the longitudinal direction of the film roll becomes longer than other parts in the width direction, and the part becomes slack. The present inventors have found through their investigation that this becomes apparent especially when the thickness difference between the recess and both ends (the thickness difference between the valley and the peak) is large. Therefore, the thickness unevenness of the recess in the width direction of the roll is important. The preferable thickness unevenness of the recess is 9% or less, and more preferably 8% or less.

[0078] In addition, in the maximum recess in the width direction thickness pattern of the polyester film roll of the present invention, the absolute value of the difference in the width direction refractive index between the maximum thickness point at either end of the recess (the thicker of the two peaks) and the minimum thickness point of the recess (the valley) is preferably 0.01 or less. If the absolute value of the difference in the width direction refractive index between the maximum thickness point at either end of the recess and the minimum thickness point of the recess is higher than 0.01, the minimum thickness point and the maximum thickness point of the recess will differ in the ease of stretching in the longitudinal direction, and a difference will occur in which they will be stretched in the longitudinal direction due to the tension during slitting. As a result, the film roll will have a long length in the longitudinal direction, and that part will become slack. The absolute value of the width direction refractive index difference is preferably 0.008 or less, more preferably 0.006 or less. The absolute value of the width direction refractive index difference is preferably low, and in the inventors' tests, 0.0003 was the lowest.

[0079] The hardness of the outermost layer of the polyester film roll of the present invention is preferably in the range of 500 to 700 as an average hardness measured at intervals of 50 mm in the width direction of the film, and the hardness variation is preferably 10% to 20%. The "outermost layer" of the film roll refers to the surface of the roll after unwinding the film from the roll and removing 5 m from the longitudinal end. The hardness is measured using a hardness tester, Paro Tester 2, manufactured by Proseo, Switzerland. If the winding hardness of the film roll surface layer is less than 500, for example, when the film roll is stored in a warehouse for half a year, the air entrained during slitting escapes, and the film roll becomes loose, which is not preferable. If the winding hardness of the film roll surface layer is higher than 700, the film roll becomes hard-wound, and the recesses are compressed as described above, which causes slackness, which is not preferable. The winding hardness of the film roll surface layer is preferably 530 to 670, and more preferably 560 to 640. In addition, the variation in hardness measured in the width direction of the film roll is preferably 10% or more and 20% or less. If it is higher than 20%, it indicates that, for example, after half a year of storing the film roll in a warehouse, there is a poor thickness unevenness in the film width direction, or that there is a tension difference in the width direction in the slitting equipment, and loosening is likely to occur after storage, which is not preferable. Also, it is preferable that it is less than 10%, and since 10% was the lower limit in the present invention, it is set to 10%. The upper limit of the variation in winding hardness in the width direction is preferably 19% or less, and more preferably 18% or less. EXAMPLES

[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of the examples, and can be modified as appropriate without departing from the spirit of the present invention. The compositions of the raw materials used in the examples and comparative examples, the film stretching methods and production conditions in the examples and comparative examples are shown in the tables.

[0081] The film was evaluated as follows. [Tg (glass transition point), Tm (melting point)] Using a differential scanning calorimeter (Seiko Denshi Kogyo Co., Ltd., DSC220), 5 mg of the unstretched film was placed in a sample pan, the pan was covered, and the temperature was increased from -40°C to 300°C at a heating rate of 10°C / min in a nitrogen gas atmosphere. Tg (°C) and Tm (°C) were determined based on JIS-K7121-1987.

[0082] [Intrinsic viscosity (IV)] 0.2 g of polyester was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (weight ratio)), and the viscosity was measured using an Ostwald viscometer at 30° C. The unit is dl / g.

[0083] [Contents of various atoms in polyester film] Quantitation was carried out by the method described below.

[0084] (a) Antimony atom 1 g of the sample was wet decomposed in a mixture of sulfuric acid and hydrogen peroxide. Sodium nitrite was then added to convert the Sb atoms to Sb 5+ Brilliant Green was added to generate a blue complex with Sb. After extracting this complex with toluene, the absorbance at a wavelength of 625 nm was measured using an absorptiometer (Shimadzu Corporation, UV-150-02), and the amount of Sb atoms in the sample was colorimetrically quantified using a calibration curve prepared in advance.

[0085] (b) Phosphorus atom The phosphorus compound was converted to orthophosphoric acid by dry decomposition of 1 g of sample in the presence of sodium carbonate, or wet decomposition in a mixture of sulfuric acid / nitric acid / perchloric acid or a mixture of sulfuric acid / hydrogen peroxide. Next, molybdate was reacted in a 1 mol / L sulfuric acid solution to produce phosphomolybdic acid, which was then reduced with hydrazine sulfate to produce heteropoly blue. The absorbance at a wavelength of 830 nm was measured using a spectrophotometer (Shimadzu Corporation, UV-150-02). The amount of phosphorus atoms in the sample was quantified using a calibration curve prepared in advance.

[0086] (c) Aluminum atom 0.1 g of the sample was dissolved in 6 M hydrochloric acid solution and left for a day, then diluted with pure water to make a 1.2 M hydrochloric acid measurement solution. The prepared solution sample was analyzed by high frequency plasma emission spectrometry.

[0087] [SRa (arithmetic mean roughness) of film surface] The surface roughness of the film was measured by the following method. Equipment: Scanning confocal laser microscope (Olympus LEXT) Laser type: 405nm semiconductor laser Objective lens: 50x Shooting mode: High precision Confocal images of the measurement surface were captured using the above equipment and conditions. Surface Roughness Analysis Measurement range: 256μm (vertical) x 256μm (horizontal) Analysis software: OLS4100 No cutoff A surface roughness analysis was performed under the above conditions, and the arithmetic mean roughness (SRa) was measured. The measurement was performed 10 times at different measurement positions, and the average value was calculated. However, if partial abnormalities such as scratches were clearly observed in the image, they were not included in the measurement value, and the measurement was repeated while avoiding the abnormal parts.

[0088] [Thickness unevenness across the entire width] The roll was placed on a slitter. After removing 5 m from the roll surface, the film roll was sampled across the entire width and 40 mm in the longitudinal direction, and the thickness in the width direction was continuously measured at 5 m / s using a continuous contact thickness meter manufactured by Micron Measuring Instruments. The maximum thickness during measurement was Tmax., the minimum thickness was Tmin., and the average thickness was Tave. The thickness unevenness in the film width direction was calculated from the following formula (1). Thickness unevenness = {(Tmax.-Tmin.) / Tave.} x 100 (%) Formula (1)

[0089] [Thickness unevenness in recesses] The continuous contact thickness in the width direction was obtained as described above, and the location of the maximum concave portion was found as shown in Figure 1. The thickness unevenness of the maximum concave portion was calculated using the following formula (2). When the heights of both ends of the maximum concave portion differed, the higher value was selected. Thickness unevenness of maximum recess = (maximum height thickness of maximum recess - minimum height thickness of maximum recess) ÷ average thickness × 100 (%) Formula (2)

[0090] [Thickness unevenness at maximum concave part in roll width direction over roll length] The roll was placed on a slitter. After that, 5 m was removed from the roll surface, and the thickness unevenness of the maximum recess in the roll width direction was measured by the method described above. After the measurement, 1000 m was rewound on the slitter, and the thickness unevenness of the recess in the roll width direction was measured by the method described above. After rewinding 1000 m, the thickness unevenness of the maximum recess in the roll width direction was repeatedly measured.

[0091] [Difference in refractive index between the maximum concave portion and both ends of the maximum concave portion] The refractive index in the width direction of the film at the maximum recess and at the position where the thickness is greater at both ends of the maximum recess was measured using an Abbe refractometer. The difference was calculated using the following formula (3) and taken as the absolute value. Difference in refractive index between the maximum recess and both ends of the maximum recess = |Refractive index in the width direction of the maximum recess - refractive index in the width direction at the higher position of both ends of the maximum recess| Formula (3)

[0092] [Friction coefficient] In accordance with JIS K-7125, a tensile tester (ORIENTEC Tensilon) was used to determine the static and dynamic friction coefficients when the front and back surfaces of the film were joined together in an environment of 23°C and 65% RH. The weight of the sled (weight) on which the upper film was wrapped was 1.5 kg, and the size of the base area of ​​the sled was 63 mm long x 63 mm wide. The tensile speed during friction measurement was 200 mm / min.

[0093] [Evaluation of slackness] A sample was taken from the film roll across the entire width and 4 to 6 m in the longitudinal direction and placed on a flat table. If any continuous strip-shaped area in the longitudinal direction was found to be worse in flatness than other areas, this was deemed to be slack. The evaluation was carried out as follows. The same evaluation was also carried out after storing the film in a warehouse at 23°C for one year. No slack: ○ There is one or more loose spots: ×

[0094] [Evaluation of winding hardness] Using a hardness tester, Paro Tester 2, manufactured by Proseo, Switzerland, measurements were taken at 50 mm intervals from the end in the roll width direction. The average value of the values ​​measured in the roll width direction was used as the measured value. The hardness variation was calculated using formula (4). (Maximum value of winding hardness in the width direction - Minimum value of winding hardness in the width direction) ÷ Average winding hardness × 100 (%) Formula (4)

[0095] Wrinkle evaluation of film rolls The polyester film rolls thus produced were visually evaluated for wrinkles on the surface of the rolls immediately after production and after storage for one year in a warehouse at a temperature of 23° C., according to the following criteria. ○: No wrinkles △: There are slight wrinkles, but the wrinkles disappear when a tension of about 20 N / m is applied to the pulled-out film. ×: There are strong wrinkles, and the wrinkles do not disappear even when a tension of about 20 N / m is applied to the pulled-out film.

[0096] [Number of defects] The obtained film roll was rewound using a rewinding machine. During rewinding, the number of defects was checked using a defect detector (model F MAX MR) manufactured by FUTEC. The number of defects 1 mm or larger in either the vertical or horizontal direction was counted. The number of defects per 10,000 square meters was calculated from the total number of defects using formula (5). Number of defects = total number of defects ÷ {film roll width (m) × film roll length (10,000 m)} Formula (5)

[0097] [printing] Immediately after the polyester film roll was produced and after it was stored in a warehouse at 23°C for one year, the film roll was gravure printed at a speed of 300 m / min with 5% dots using a gravure printing machine (manufactured by Azumaya Iron Works Co., Ltd.). The ink used was gravure printing ink (manufactured by Toyo Ink Co., Ltd.: product name Fine Star R92 ink) mixed with a dilution solvent (manufactured by Toyo Ink Co., Ltd.: product name SL302) in a ratio of 77:23. The obtained print sample was rewound using a rewinding machine. When rewinding, the number of print defects was investigated using a defect detector (model F MAX MR) manufactured by FUTEC Co., Ltd. The number of print defects of 1 mm or more in either the vertical or horizontal direction was calculated. The number of print defects per 10,000 square meters was calculated from the total number of print defects using formula (6). Number of printing defects = total number of printing defects ÷ {film roll width (m) × film roll length (10,000 m)} (Formula 6)

[0098] <Preparation of polymerization catalyst solution> (Ethylene glycol solution of phosphorus compounds) 2.0 liters of ethylene glycol was added to a flask equipped with a nitrogen inlet tube and a cooling tube at room temperature and normal pressure, and then 200 g of Irganox1222 (manufactured by BASF Co., Ltd.), a phosphorus compound represented by chemical formula (4), was added while stirring at 200 rpm under a nitrogen atmosphere. After adding another 2.0 liters of ethylene glycol, the jacket temperature was changed to 196°C and the temperature was raised, and from the point when the internal temperature reached 185°C or higher, the mixture was stirred under reflux for 60 minutes. After that, the heating was stopped, the solution was immediately removed from the heat source, and the mixture was cooled to 120°C or lower within 30 minutes while maintaining the nitrogen atmosphere.

[0099] (Aluminum compound in ethylene glycol) 5.0 liters of pure water was added to a flask equipped with a cooling tube at room temperature and normal pressure, and then 200 g of basic aluminum acetate (hydroxyaluminum diacetate) was added as a slurry with pure water while stirring at 200 rpm. Further, pure water was added so that the total volume was 10.0 liters, and the mixture was stirred at room temperature and normal pressure for 12 hours. The jacket temperature was then changed to 100.5°C and the temperature was raised, and from the point when the internal temperature reached 95°C or higher, the mixture was stirred under reflux for 3 hours. Stirring was stopped and the mixture was allowed to cool to room temperature. If undissolved particles were observed at that time, the solution was filtered with a glass filter (3G) to obtain an aqueous solution of an aluminum compound. Next, 2.0 liters of the aqueous solution of the aluminum compound and 2.0 liters of ethylene glycol were charged into a flask equipped with a distillation apparatus at room temperature and normal pressure, and after stirring at 200 rpm for 30 minutes, a uniform water / ethylene glycol mixed solution was obtained. Next, the jacket temperature was changed to 110°C and the temperature was raised, and water was distilled off from the solution. When the amount of distilled water reached 2.0 liters, heating was stopped and the solution was allowed to cool to room temperature, thereby obtaining an ethylene glycol solution of the aluminum compound.

[0100] In the following, "parts" refers to "parts by mass". 2130 parts of terephthalic acid, 1955 parts of ethylene glycol, and 0.7 parts of triethylamine were added to a reactor equipped with a stirrer, a thermometer, and a distillation cooler, and the temperature was gradually raised from 220°C to 250°C under a pressure of 0.35 MPa, and an esterification reaction was carried out while removing the distilled water from the system. Next, the polymerization catalyst solution was added to an ethylene glycol solution of a phosphorus compound and an ethylene glycol mixed solution of an aluminum compound so that the phosphorus atom was 0.047 mol% and the aluminum atom was 0.021 mol% relative to the dicarboxylic acid component in the polyester resin, and then the initial polymerization was carried out under reduced pressure to 1.3 kPa over 1 hour, the pressure was raised to 270°C, and the final polymerization was carried out at 0.13 kPa or less to obtain a polyester resin.

[0101] The polyesters used in the examples and comparative examples are as follows: Polyester 1: Polyethylene terephthalate (IV 0.73 dl / g) Polyester 2: Polyethylene terephthalate (IV 0.73 dl / g) to which SiO2 (spherical silica with an average particle size of 2 μm) was added as a lubricant in the production of polyester 1 above at a ratio of 7,500 ppm to the polyester.

[0102] [Table 1]

[0103] Example 1 The polyester 1 and polyester 2 were mixed in a weight ratio of 96:4 and fed into an extruder. The mixed resin was then melted at 270°C, cooled to 260°C, extruded from a T-die, and rapidly cooled by being wound around a rotating metal roll cooled to a surface temperature of 30°C to obtain an unstretched film having a thickness of 220 μm. The take-up speed of the unstretched film (the rotation speed of the metal roll) was about 80 m / min. The Tg and Tm of the unstretched film were 75°C and 256°C, respectively. A laser cleaner was installed on the cooling metal roll to prevent adhesion of foreign matter. The unstretched sheet obtained was heated to 110°C and stretched in the longitudinal direction at a total stretch ratio of 4.5 times by two-stage stretching, 1.5 times in the first stage and 3 times in the second stage. Subsequently, in a transverse stretching process (hereinafter referred to as tenter), the sheet was stretched in the width direction at a temperature of 130°C by 2 times in the first stage and 2.3 times in the second stage at a total stretch ratio of 4.6 times (see Figure 2). After stretching in the width direction at 4.6 times, the sheet was heat-set at 243°C and heat-relaxed by 5% in the width direction. The film after heat relaxation was cooled to 50°C or less in the tenter, and the oligomer was sucked in the width direction over the entire width of the film by the exhaust device shown in Figure 3 at the exit of the tenter. Next, both ends of the stretched film were cut and removed, and the film was then subjected to corona discharge treatment and wound into a roll by a winder to produce a master roll of biaxially stretched polyester film with a thickness of 12 μm, a width of 8 m, and a winding length of 85,000 m. The biaxially stretched film obtained above was slit with a slitter into widths of 4000 mm, 2000 mm, and 1000 mm so as to have a roll length of 80000 m. A 6-inch metal core was used.

[0104] Specific slitting conditions were as follows: slitting was started with an initial tension of 150N / m and an initial surface pressure of 330N / m. As the winding length increased from 1000m to 79000m, the tension was reduced at a constant rate from 150 to 80N / m. Slitting was also performed with a constant surface pressure of 330N / m. The film production process conditions and slitting conditions are shown in Table 2. The properties of the obtained film were evaluated by the above-mentioned methods. The evaluation results are shown in Tables 3 and 4. A film with the target properties was obtained, and the slackness was good. Regarding the slackness, in addition to the results in Table 3 (surface layer of the film roll), all samples every 1000 m were evaluated, and the results were ○ (no slackness) for all samples of the above three film rolls.

[0105] Example 2 A biaxially stretched polyester film roll was obtained in the same manner as in Example 1, except that polyester 1 and polyester 2 were mixed in a weight ratio of 94:6 and fed into the extruder. The film-forming process conditions and slitting conditions are shown in Table 2, and the evaluation results are shown in Tables 3 and 4. The film was of good quality.

[0106] Example 3 A biaxially oriented polyester film roll was obtained in the same manner as in Example 1, except that the thickness of the film was changed to 6 μm and the roll length was changed to 30,000 m. The film-forming process conditions and slitting conditions are shown in Table 2, and the evaluation results are shown in Tables 3 and 4. The film was of good quality.

[0107] Comparative Example 1 The slitting conditions were as follows: initial tension was 120 N / m, and initial surface pressure was 280 N / m. The tension was reduced at a constant rate from 120 to 50 N / m as the winding length increased from 1000 m to 79000 m. Slitting was performed with a constant surface pressure of 280 N / m. Other than the slitting conditions, the film was produced under the same conditions as in Example 1. The film-forming process conditions and slitting conditions are shown in Table 2, and the evaluation results are shown in Tables 3 and 4. The winding hardness was low, and the appearance of the film roll after storage in the warehouse and the film slack were poor. In addition, there was a large number of print defects after long-term storage.

[0108] Comparative Example 2 The unstretched sheet obtained in the same manner as in Example 1 was heated to 110°C, and stretched in the longitudinal direction at a total stretch ratio of 3 times by two-stage stretching, 1.5 times in the first stage and 2 times in the second stage. Subsequently, in a transverse stretching process (hereinafter referred to as tenter), the sheet was stretched in the width direction at a total stretch ratio of 4.6 times by two-stage stretching at a temperature of 140°C in the first stage and 2.3-stage stretching at a temperature of 170°C in the second stage. After stretching in the width direction at 4.6 times, the sheet was heat-set at 243°C and heat-relaxed by 5% in the width direction. The film after heat relaxation was cooled to 50°C or less in the tenter, and the oligomer was sucked in the width direction by the exhaust device shown in Figure 3 at the exit of the tenter. Next, both ends of the stretched film were cut and removed, and then the film was subjected to corona discharge treatment and wound into a roll by a winder to produce a master roll of biaxially stretched polyester film having a thickness of 12 μm, a width of 8 m, and a winding length of 35,000 m. Specific slitting conditions were as follows: slitting was started with an initial tension of 150 N / m and an initial surface pressure of 330 N / m. The tension was reduced at a constant rate from 150 to 80 N / m as the roll length increased from 1000 m to 29000 m. Slitting was performed with a constant surface pressure of 330 N / m to obtain a film roll with a roll length of 30000 m. The film-forming process conditions and slitting conditions are shown in Table 2, and the evaluation results are shown in Tables 3 and 4. The thickness was uneven in the width direction, the winding hardness varied widely, and the appearance and slackness of the film roll were also poor, resulting in a polyester film roll of inferior quality.

[0109] [Table 2]

[0110] [Table 3]

[0111] [Table 4] [Industrial Applicability]

[0112] Since the biaxially oriented polyester film roll of the present invention has good slackness as described above, it can be suitably used in processing such as printing.

Claims

1. A biaxially stretched polyester film roll for packaging is wound up, the film being made of a polyethylene terephthalate composition which may contain 5% by mass or less of a resin component other than polyester, the antimony content in the film being 10 ppm or less, the phosphorus content in the film being 25 ppm or more and 75 ppm or less, the film being titanium-free, the film containing 1% by weight or less of inorganic particles, and the arithmetic mean roughness of the film surface being 0.02 μm or more and 0.05 μm or less, the biaxially stretched polyester film roll for packaging being characterized in that the biaxially stretched polyester film and the film roll satisfy the following requirements (1) to (6). (1) The length of the film roll is 8,000 m or more and 80,000 m or less. (2) Film roll width is 500 mm or more and 4000 mm or less (3) The hardness of the outermost layer of the film roll is in the range of 500 to 700 on average when measured at intervals of 50 mm in the width direction of the film. (4) The hardness of the outermost layer of the film roll has a variation of 10% to 20% when measured at intervals of 50 mm in the width direction of the film. (5) Film thickness is 5 μm or more and 40 μm or less (6) In the thickness unevenness in the film width direction on the surface layer of the film roll, the thickness pattern has a recessed portion, and in the recess with the largest thickness difference (maximum recess), the thickness unevenness of the maximum recess calculated from the maximum thickness difference in the maximum recess and the average thickness of the film is less than 10%.

2. 2. The biaxially stretched polyester film roll for packaging according to claim 1, wherein the thickness unevenness in the width direction of the film of each sample sampled at intervals of 1000 m along the winding length from the surface layer of the film roll is 10% or less for all samples, the thickness unevenness being calculated from the maximum thickness difference at the maximum recess and the average thickness of the film.

3. 3. The biaxially stretched polyester film roll for packaging according to claim 1, wherein the absolute value of the difference in the width direction refractive index between the maximum recess and either of the maximum thickness points at both ends of the recess is 0.010 or less.

4. 4. The biaxially oriented polyester film roll for packaging according to claim 1, wherein the number of defects of 1 mm or more per 10,000 square meters of film is 1.0 or less.

5. 5. The biaxially stretched polyester film roll for packaging according to claim 1, wherein the static friction coefficient and the dynamic friction coefficient of the outer surface and the inner surface of the film roll are both 0.1 or more and 0.8 or less.

6. 6. The biaxially stretched polyester film roll for packaging according to claim 1, wherein the intrinsic viscosity of the film is 0.51 dl / g or more and 0.70 dl / g or less.

Citation Information

Patent Citations

  • Polyester film for masking tape of photomask

    JP2008248135A

  • Biaxially oriented polyester film and method for producing the same

    JP2018162435A

  • Thermochromic film and thermochromic composite body

    WO2017077797A1

  • Polyester film

    WO2017169553A1

  • Method of winding film into roll

    JP1988252853A